Community and Social Interaction in Digital Religious Discourse in Nigeria, Ghana and Cameroon - Chiluwa, Innocent (Journal of religion, media and digital culture, 2013)
Since the advent of the Internet, religion has maintained a very strong online presence. This study examines how African Christianity is negotiated and practised on the Internet. The main objectives are to investigate to what extent online worshippers in Nigeria, Ghana and Cameroon constitute (online) communities and how interactive the social networks of the churches are. This study shows that some important criteria for community are met by African digital worshippers. However, interaction flow is more of one to many, thus members do not regularly interact with one another as they would in offline worship. Worshippers view the forums as a sacred space solely for spiritual matters and not for sharing social or individual feelings and problems. However, the introduction of social media networks such as Facebook, Twitter, YouTube and interactive forums is an interesting and promising new development in religious worship in Africa.